(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Word stress is one of the central concepts of English phonetics and a fundamental component of spoken communication. In every polysyllabic word of English, one syllable is pronounced more prominently than the others. This prominence affects not only the rhythm and melody of speech but also the meaning and grammatical function of word. Inaccurate stress placement can lead to misunderstanding, miscommunication, or foreign-sounding pronunciation.